Gambaran Pengetahuan dan Sikap Ibu serta Peran Kelompok Pendukung ASI terhadap Pemberian ASI Eksklusif (Studi Kasus di Desa Kekeran Kecamatan Mengwi) - Putu Sannia Dewi; Anak Agung Ayu Lila Paramasatiari; I Wayan Darwata (Aesculapius Medical Journal, 2023)
Exclusive breastfeeding is not giving other food or drink (including water) to the baby for six months. From the predetermined target (60%), the coverage of exclusive breastfeeding at the Mengwi I Health Center was 53.69% (2019). This figure changes each year, so improvements in nutritional status must be carried out and maintained continuously. In order to realize the exclusive breastfeeding target of 60%, the government has provided many programs, one of which is the Breastfeeding Support Group (KP-ASI). KP-ASI is a group of pregnant women who exchange information to optimize breastfeeding. Based on the 2019 activity report in Kekeran Village, Mengwi I Health Center, the intensity of breastfeeding has increased from 87% to 96%. This study was done to describe the knowledge and attitudes of mothers and the role of KP-ASI in exclusive breastfeeding in Kekeran Village, Mengwi District. The design of this research is descriptive quantitative with case study method. The population is the mothers of KP-ASI participants in Kekeran Village, Badung Regency. The results showed that all subjects in this study (100.0%) generally had a good knowledge of exclusive breastfeeding. Most of the subjects in this study had a good attitude in exclusive breastfeeding, as many as 18 people (66.7%). Most of the subjects in this study have a good role of KP-ASI, as many as 26 people (96.3%).